Pengaruh Tambahan Penghasilan Pegawai Terhadap Kinerja Pegawai di Sekretariat Daerah Provinsi Sulawesi Tenggara - Bake, Jamal; Marghana, Revisya Alita; Merliyana, Merliyana (e-JKPP, 2024)
This study aims to analyse the effect of additional employee income on performance at the Regional Secretariat of Southeast Sulawesi Province. The research method used is quantitative descriptive analysis. The population of this study consisted of 64 employees who were Civil Servants or State Civil Apparatus who worked at the Secretariat in the southeast Sulawesi Province. This study used a total sampling approach, by including all employees as samples. Data collection was carried out using a closed questionnaire with a Likert scale, while data analysis was carried out using descriptive statistics and simple linear regression. The results showed that additional income had a positive and significant effect on employee performance at the Regional Secretariat of Southeast Sulawesi Province. For future research, it is recommended to focus on analysing the indicators of Employee Performance Allowance based on the theories of experts and not only rely on laws or regulations. In addition, future research can explore other factors outside the current research model that may affect employee performance, beyond the scope of the Employee Performance Allowance.